Survey Penggunaan Media Pembelajaran Information and Communication Technology (ICT) Oleh Guru PJOK Sekolah Menengah Pertama di Kabupaten Bima (Universitas Negeri Semarang, 2022)
Education is the spearhead of the nation's progress learning physical education, sports and health, the balance of affective, cognitive, and psychomotor aspects must be considered, with the aim that learning is achieved optimally. The use of ICT-based learning media by junior high school physical education teachers which aims to assist the learning process and improve the quality of learning. This study aims to determine how much use of ICT-based learning media in Bima district area. Quantitative research methods using survey methods, and collects information or data using questionnaires and interviews. Research that takes a sample from a population and uses a questionnaire as the main data collection tool. The sample of this reasearch is physical education teachers at Junior High Schools in Bima Distric 27 teachers. The use of ICT-based learning media helps physical education teachers in the learning process, the average usage is 22.22% very good category, 37.04% good category, 33.33% poor category and 7.41% very poor category. In this study it can be concluded that the development of learning materials using ICT-based media by physical education teachers in junior high schools in Bima District are included in the good category.